Analisis Produktivitas Pekerja Pada Pekerjaan Pondasi dan Pemasangan Batu Bata Dengan Metode Work Study - Muhamad Fauzan Endar; Rahma Ramadhani; Meriana Wahyu Nugroho; Titin Sundari (Jurnal Sipil Terapan, 2023)
Work productivity is an element where the success of a project requires effective time and cost. This study aims to determine the productivity of foundation and brick workers. The work study method is an operations management technique used to increase work efficiency. The results of the analysis on foundation work with 2 groups (1 worker and 1 worker) using work study and AHSP 2021 for 1m3 with 1:3:10 specs obtained a productivity of 12.92 1m3 for 3 working days with a cost per 1m3 using the work study method, namely Rp.639,306 and AHSP 2021 Rp.782,517 with a difference of Rp. 143,211. The total cost of workers in foundation work using the work study method is IDR 8,257,273 and the 2021 AHSP is IDR 10,106,990 with a difference of IDR 1,849,717. In brick work with 1 group (1 mason 1 worker) using work study and AHSP 2021 for 1m2 with 1:3:10 specs, the productivity is 106.99 m2 for 9 working days with a cost per 1m2 using the work study method, namely Rp.60,696 and AHSP 2021 Rp.68,834 with a difference of Rp.8,138. The total cost of workers on brick work using the work study method is IDR 6,488,408 and AHSP 2021 is IDR 7,358,312 with a difference of IDR 869,904.